Application of Rapid Application Development Method in Designing Knowledge Management System to Improve Employee Knowledge and Performance at Ministry of Agriculture - Palupiningtyas, Dyah; Dewi Maria, Aletta; Adhistyo Wijoyo, Tuwuh; Prarasdya Alyka, Amara; Putri Brawarso, Kaila Zefanya (Jurnal Informasi dan Teknologi, 2024)
This research aims to design and build a knowledge management system that can accommodate, manage, and disseminate knowledge to increase employee knowledge. In this research, data collection was obtained in three ways, including observation, interviews, a literature study, and a study of similar literature. The author uses the building block knowledge management method, unified modeling language (UML), to design a web-based system with a user interface that is quite easy to use. In this research, the author uses an object-oriented system development method, namely rapid application development (RAD), which uses unified modeling language tools to describe use case diagrams. Based on the research results, it was found that the KMS was built on a web basis using the RAD (rapid application development) approach and UML (unified modeling language) notation for system analysis design and PHP and MySQL for coding and databases. Before the existence of KMS, searching for documents could take 10 minutes, whereas after the KMS application, users only need five minutes to search for stored documents, resulting in a time efficiency of nine minutes. This system also helps employees communicate with each other anytime and anywhere by creating new discussion topics. Apart from fostering a culture of knowledge sharing, discussion forums in this system can be used as a place for employees to collaborate and find solutions.